Official Financial Flows, Capital Mobility, and Global Imbalances - Bayoumi, Tamim (IMF Working Papers; Working Paper ;, 2014)
We use a cross-country panel framework to analyze the effect of net official flows (chiefly foreign exchange intervention) on current accounts. We find that net official flows have a large but plausible effect on current account balances. The estimated effects are larger with instrumental variables (42 cents to the dollar on average compared to 24 without instruments), reflecting a possible downward bias in regressions without instruments owing to an endogenous response of net official flows to private financial flows. We consistently find larger impacts of net official flows when international capital flows are restricted and smaller impacts when capital is highly mobile. A further result is that there is an important positive effect of lagged net official flows on current accounts that we believe operates through the portfolio balance channel.